Blockchain based e-voting system with homomorphic encryption and threshold signature - Probor, Mushfique Nasir; Ahmed, Mursalin; Kabir, Sharika Bintey; Fuad, Md. Muhtasim; Bushra, Tasnim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.